Solvent-dependent inversion of circular dichroism signal in naproxen: An unusual effect! - Ximenes, Valdecir Farias [UNESP]; Morgon, Nelson Henrique; Souza, Aguinaldo Robinson de [UNESP] (Wiley-Blackwell, 2018)
The electronic circular dichroism (ECD) spectra of naproxen enantiomers were studied as a function of solvents using experimental (circular dichroism) and theoretical (time-dependent density functional theory) approaches. The (R)- and (S)-naproxen enantiomers presented an unusual inversion in their ECD signals in the presence of ethanol and water when compared with polar aprotic solvents such as acetonitrile. From a practical point of view, these findings deserve great attention because these solvents are widely used for high-performance liquid chromatography analysis in quality control of chiral pharmaceutical drugs. This is particularly relevant to naproxen because the (S)-naproxen has anti-inflammatory properties, whereas (R)-naproxen is hepatotoxic. A time-dependent density functional theory computer simulation was conducted to investigate the signal inversion using the solvation model based on density, a reparameterization of polarized continuum model. Electronic circular dichroism signals of conformers were calculated by computer simulation and their contribution to the combined spectra obtained according to Boltzmann weighting. It was found that the experimentally observed ECD signal inversion can be associated with the minor or major contribution of different conformers of naproxen.
Keywords: Boltzmann weighting; electronic circular dichroism; enantiomers; naproxen; solvent effect; time-dependent density functional theory